Developing a model of competency and expertise certification tests for vocational high school students - Pardjono Pardjono; Sugiyono Sugiyono; Aris Budiyono (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2015)
This study aims to: (1) develop, produce, and investigate the appropriateness model of competency and expertise certification tests for vocational high school (VHS) students of the Mechanical Engineering expertise competency.To attain the objectives, the researcher conducted a research and development study consisting of 10 steps. The research product was validated by experts, VHS teachers, and lecturers at Mechanical Engineering Education through Focus Group Discussion (FGD), and the field tryout conducted at SMK Warga Surakarta and SMK Bhineka Karya Simo, Boyolali, Central Java. The results of the study are. (1) The study produces a model of Competency and Expertise Certification Tests Based on the School Production Unit (CECT_SPU) for VHS Students of the Mechanical Engineering Expertise Competency; (2) The CECT_SPU model satisfies the criteria for a good modelby a mean score of 3.557; (3) The mean score of the model implementation in the tryouts were 3.670 in the individual tryout and 3.730 in the small-group tryout; (4) The CECT_SPU model satisfies the criteria for an effective modelby a mean score of 3.730; (5) The CECT_SPU model satisfies the criteria for an efficient modelby a mean score of 3.780; (6) The CECT_SPU model satisfies the criteria for a practical model; by a mean score of 3.700.